2001
DOI: 10.1007/s00784-001-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of four root canal sealers against endodontic pathogens

Abstract: The antibacterial effects of various types of widely used endodontic sealers have not been compared systematically on facultative or obligate anaerobic endodontic pathogens. The aim of this study was to evaluate the antimicrobial properties of four commonly used endodontic sealers: two epoxy-resin-based sealers (AH26, AH plus), one zinc-oxide eugenol-based sealer (N2), and one calcium hydroxide-based sealer (Sealapex). The testing microbes were four facultative anaerobic species (Streptococcus mutans, Streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 21 publications
2
39
1
2
Order By: Relevance
“…Hence, it cannot be conclusively said that Chitra HAP-Fil would have no effect on any other strains of the same organism.With zinc oxide eugenol, antibacterial property was observed against both S.aures and E.faecalis by both methods. These finding were similar to that of White et al , Lai et al [19,20] . This pronounced antimicrobial effect may be due to the intimate contact of the medicament with the pathogen in the various cell studies, which is less probable in the root canal system.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it cannot be conclusively said that Chitra HAP-Fil would have no effect on any other strains of the same organism.With zinc oxide eugenol, antibacterial property was observed against both S.aures and E.faecalis by both methods. These finding were similar to that of White et al , Lai et al [19,20] . This pronounced antimicrobial effect may be due to the intimate contact of the medicament with the pathogen in the various cell studies, which is less probable in the root canal system.…”
Section: Discussionsupporting
confidence: 92%
“…We selected S. mutans because it is the most significant cariogenic microorganism in the mouth [Tanzer et al, 2001], although clearly the order of activity might vary with different bacterial strains. Lai et al [2001] demonstrated variation in inhibitory effect, not only between different materials, but between bacterial strains.…”
Section: Bacterial Growthmentioning
confidence: 99%
“…Furthermore, sealers that possess both optimum flow ability and antimicrobial properties might theoretically eliminate residual microorganisms located in confined areas of the root canal system 6,7 . Studies have reported that several endodontic sealers have antimicrobial effects [8][9][10] . Sealers having antimicrobial effects may help to eliminate residual microorganisms unaffected by the influence of both chemomechanical preparation and intracanal medication.…”
mentioning
confidence: 99%